Facile synthesis of strontium/calcium aluminate-based persistent phosphors for enhanced functionally additive manufacturing - Yukun Li; Ke Chen; Jiaren Du; Hengli Zhu; Jiaping Zhang; Sisi Wang; Senkai Ye; Hengwei Lin (Chemical Engineering Journal, 2026)

The climate effects of ultrafine particles: uncertainties and future perspectives - Yuzhi Jin; Jiandong Wang; Shang Wu; Zhouyang Zhang; Jiaping Wang; Zeyuan Tian; Bin Wang; Qihao Lin; Jing Cai; Chenxi Li; Lei Yao; Chao Liu; et al. (ENGINEERING Environment, 2026)

Functional reorganization of microbial ecological clusters is associated with citrus soil health enhancement under greenhouse cultivation - Chenhong Liu; Qi Zhao; Lin Zhang; Fuzhi Ke; Xuebin Xu; Senxiang Yu; Jiaping Lang; Tida Ge; Cong Wang; Haoqing Zhang (Plant and Soil, 2026)

Modeling of longwave radiation on coastal building façades based on field measurements - Kaili Yin; Xiaojing Zhang; Jingchao Xie; Haicheng Yang; Jingjie Tan; Fen Lin; Jiaping Liu (Building and Environment, 2026)

Emulsifier-free gelatin-based intelligent films with long-term antimicrobial and antioxidative activities - Shuhua Lin; Jiaping Shen; Shuhong Zheng; Xingli Zheng; Xu Chen; Xixi Cai; Yapeng Fang; Shaoyun Wang (Food Hydrocolloids, 2025)

Molecular detection and phylogenetic analysis of lumpy skin disease virus in Yunnan Province, China from 2019 to 2023 - Jun Yao; Xue Li; Lei Tan; Lin Gao; Pei Zhu; Jiarui Xie; Rui Yan; Taoyin Yu; Fengyi Xia; Qiyun Chen; Bangquan Zeng; Jiaping Yang (Veterinary Research Communications, 2025)

Transformation of exogenous hexavalent chromium in soil: Factors and modelling - Ying Li; Jiaping Lin; Yang Wu; Song Jiang; Chaoran Huo; Tongxu Liu; Yang Yang; Yibing Ma (Journal of Hazardous Materials, 2024)

Transitioning weathered oil fields towards new energy: A review on utilizing hydrogenotrophic methanogens for petroleum hydrocarbons remediation - Jiaping Zhou; Wei-Han Lin; Ying-Liang Yu; Cheng-Di Dong; Haibing Zhang; Zhongtao Hu; Chih-Ming Kao (Journal of Hazardous Materials, 2024)

Co-delivery of indomethacin and uricase as a new strategy for inflammatory diseases associated with high uric acid - Jie Liu; Chenshi Lin; Man Wu; Yingjie Wang; Shenyu Chen; Taiwang Yang; Chenlu Xie; Yue Kong; Wenliang Wu; Jiaping Wang; Xiaonan Ma; Chao Teng (Drug Delivery and Translational Research, 2024)

Noise resistant steam generator water level reconstruction for nuclear power plant based on deep residual shrinkage network - Peng Yue; Faming Fang; Peng Xu; Hongyun Xie; Qizhi Duan; Jiaping Lin; Liyang Xie (Annals of Nuclear Energy, 2023)

Emulsifier free fish gelatin based films with excellent antioxidative and antibacterial activity: Preparation, characterization and application in coating preservation of fish fillets - Gaojie Song; Sheng Lin; Yuesheng Wu; Jiaping Shen; Jiulin Wu; Wenjin Zhu; Shuna Yu; Jianhua Li; Shaoyun Wang (Journal of Food Engineering, 2023)

Full-Length Transcriptome of Red Swamp Crayfish Hepatopancreas Reveals Candidate Genes in Hif-1 and Antioxidant Pathways in Response to Hypoxia-Reoxygenation - Yu Xu; Hai Lin; Weihui Yan; Jiajia Li; Mengling Sun; Jiaping Chen; Zhiqiang Xu (Marine Biotechnology, 2022)

Stocks and losses of soil organic carbon from Chinese vegetated coastal habitats - Chuancheng Fu; Yuan Li; Lin Zeng; Haibo Zhang; Chen Tu; Qian Zhou; Kuanxu Xiong; Jiaping Wu; Carlos M. Duarte; Peter Christie; Yongming Luo (Global Change Biology, 2021)
Global vegetated coastal habitats (VCHs) represent a large sink for organic carbon (OC) stored within their soils. The regional patterns and causes of spatial variation, however, remain uncertain. The sparsity and regional bias of studies on soil OC stocks from Chinese VCHs have limited the reliable estimation of their capacity as regional and global OC sinks. Here, we use field and published data from 262 sampled soil cores and 181 surface soils to report estimates of soil OC stocks, burial rates and losses of VCHs in China. We find that Chinese mangrove, salt marsh and seagrass habitats have relatively low OC stocks, storing 6.3 ± 0.6, 7.5 ± 0.6, and 1.6 ± 0.6 Tg C (±95% confidence interval) in the top meter of the soil profile with burial rates of 44 ± 17, 159 ± 57, and 6 ± 45 Gg C/year, respectively. The variability in the soil OC stocks is linked to biogeographic factors but is mostly impacted by sedimentary processes and anthropic activities. All habitats have experienced significant losses, resulting in estimated emissions of 94.2–395.4 Tg CO 2 e (carbon dioxide equivalent) over the past 70 years. Reversing this trend through conservation and restoration measures has, therefore, great potential in contributing to the mitigation of climate change while providing additional benefits. This assessment, on a national scale from highly sedimentary environments under intensive anthropogenic pressures, provides important insights into blue carbon sink mechanism and sequestration capacities, thus contributing to the synchronous progression of global blue carbon management.

Spatial variability assessment of La and Nd concentrations in coastal China soils following 1000 years of land reclamation - Lin Wang; George Christakos; Chunfa Wu; Jiaping Wu (Journal of Soils and Sediments, 2020)

Resource (Light and Nitrogen) and Density-Dependence of Seaweed Growth - Xi Xiao; Susana Agusti; Fang Lin; Caicai Xu; Yan Yu; Yaoru Pan; Ke Li; Jiaping Wu; Carlos M. Duarte (Frontiers in Marine Science, 2019)

Differential Effects of Paclobutrazol on the Bulblet Growth of Oriental Lily Cultured In Vitro: Growth Behavior, Carbohydrate Metabolism, and Antioxidant Capacity - Yun Wu; MinYi Sun; JiaPing Zhang; Lin Zhang; ZiMing Ren; RuiHan Min; XiuYun Wang; YiPing Xia (Journal of Plant Growth Regulation, 2019)

A large meta-analysis of the global prevalence rates of S. aureus and MRSA contamination of milk - Qianting Ou; Junli Zhou; Dongxin Lin; Chan Bai; Ting Zhang; Jialing Lin; Haoqu Zheng; Xiaojie Wang; Jiaping Ye; Xiaohua Ye; Zhenjiang Yao (Critical Reviews in Food Science and Nutrition, 2018)

Screening of seaweeds in the East China Sea as potential bio-monitors of heavy metals - Yaoru Pan; Thomas Wernberg; Thibaut de Bettignies; Marianne Holmer; Ke Li; Jiaping Wu; Fang Lin; Yan Yu; Jiang Xu; Chaosheng Zhou; Zhixing Huang; Xi Xiao (Environmental Science and Pollution Research, 2018)

Endophytic Diaporthe from Southeast China are genetically diverse based on multi-locus phylogeny analyses - Jiaying Wang; Xihui Xu; Lijuan Mao; Jiaping Lao; Fucheng Lin; Zhilin Yuan; Chulong Zhang (World Journal of Microbiology and Biotechnology, 2014)

Evaluation of MODIS surrogates for meteorological humidity data in east Africa - Shengpan Lin; Nathan J. Moore; Joseph P. Messina; Jiaping Wu (International Journal of Remote Sensing, 2013)

Protection of guinea pigs by vaccination with a recombinant swinepox virus co-expressing HA1 genes of swine H1N1 and H3N2 influenza viruses - Jiarong Xu; Deji Yang; Dongyan Huang; Jiaping Xu; Shichao Liu; Huixing Lin; Haodan Zhu; Bao Liu; Chengping Lu (Archives of Virology, 2013)

Evaluating DEM source and resolution uncertainties in the Soil and Water Assessment Tool - Shengpan Lin; Changwei Jing; Neil A. Coles; Vincent Chaplot; Nathan J. Moore; Jiaping Wu (Stochastic Environmental Research and Risk Assessment, 2013)

Spatiotemporal dynamics of soil erosion risk for Anji County, China - Zhenlan Jiang; Shiliang Su; Changwei Jing; Shengpan Lin; Xufeng Fei; Jiaping Wu (Stochastic Environmental Research and Risk Assessment, 2012)